1975
DOI: 10.1159/000152734
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of Dermatoglyphic Patterns in Twins

Abstract: Analysis of variance was performed on 71 dermatoglyphic variables in 424 twin sets. Using a method of twin analysis estimates of genetic variance were obtained. 54 of the variables were quantitated using a scoring system with modifications of arch or no pattern = 0, loops = 1, whorl = 2. The results indicated a significant genetic influence in most pattern areas. Patterning was more genetically controlled in the hand than in the foot. The hallucal area had the most significant genetic component of the foot whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
2

Year Published

1977
1977
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 7 publications
1
26
2
Order By: Relevance
“…In the NHLBI Twin Study, 15 of 31 quantitative variables were found to have significant evidence (P < 0.05) for unequal total variance of MZ and DZ twins [9]. Reed et al [20] reported that 20 of 71 dermatoglyphic variables had significantly (P < 0.05) unequal total variances for MZ and DZ twins. Association of twin type with the variance of quantitative traits, therefore, does not appear to be unusual.…”
Section: Test For Association Of Total Variance With Twin Typementioning
confidence: 99%
“…In the NHLBI Twin Study, 15 of 31 quantitative variables were found to have significant evidence (P < 0.05) for unequal total variance of MZ and DZ twins [9]. Reed et al [20] reported that 20 of 71 dermatoglyphic variables had significantly (P < 0.05) unequal total variances for MZ and DZ twins. Association of twin type with the variance of quantitative traits, therefore, does not appear to be unusual.…”
Section: Test For Association Of Total Variance With Twin Typementioning
confidence: 99%
“…For example, ridge-patterns are first differentiated on fingers and then on toes, palms, and soles (Bonnevie, 1929; Cummins, 1929; Hale, 1952; Kollmann, 1883; Mukherjee, 1978Mukherjee, , 1980; Okajima, 19751. The heritability is the greatest on fingers, and less and less on toes, palms, and soles (Loesch, 1971(Loesch, , 1974(Loesch, , 1983; Mukherjee, 1966Mukherjee, , 1967; Mukherjee and Sirajuddin, 1974; Reed et al, 1975; Redd et al, which are perhaps the earliest to arise, display about the stron est influence of heredThus, if the environmental influence on all dermatoglyphic traits is largely that of the in utero conditions, it would be reflected in birth order effects as in the case of birth weight (Karn and Penrose, 1951) or in maternal age effects as in some congenital malformations (Parsons, 1964; Penrose, 1954a), and such effects would increase with the eriod of emb ogenesis of the traits. So far, been re orted for ab ridge-counts on palms in 1972; I F oesch, 1971,1974,1983; Mukherjee, lier are more % eritable than those developing 1979).…”
Section: 1967; and Others)mentioning
confidence: 99%
“…[2]: the scoring system used followed that of Reed cl al. [8] with slight modifications (table I). Two kinds of estimates were obtained: a within-pair (Gw) and a combined among within-pair estimate (Gt ).…”
Section: Holt [41mentioning
confidence: 99%
“…It has been clearly demonstrated that the qualitative characters follow a 'continuum' of com plexity and investigations have been made searching for an adequate classi fication. Reed et al [8] used a scoring method combining aspects of both pattern type and size, derived from the original system of Penrose and Loesch [7], They obtained estimates of genetic variance for several palmar and plantar variables, which were assessed by the method of Christian et al [2], In a previous paper [6], we have presented dermatoglyphic data from an unselected series of monozygotic (MZ) and dizygotic (DZ) twins, but the qualitative traits were studied using percentage of concordance only and Holzinger's [5] somewhat unsatisfactory formula. Therefore, we decided to reanalyze the information related to the hypothenar.…”
Section: Introductionmentioning
confidence: 99%